LAMPUNG LOCAL WISDOM AS A BASIS FOR DEVELOPING PARENTING PATTERNS TO IMPROVE STUDENTS' FRUGAL LIVING - Tiara Oktavia; Risma Margaretha Sinaga; Rahma Kurnia Sri Utami (ACADEMIA: Jurnal Inovasi Riset Akademik, 2026)
ABSTRACT The phenomenon of excessive consumption that is increasingly embedded in adolescents’ lives in the digital era presents new challenges for character education, particularly in fostering wise financial management habits. In this context, local cultural values have the potential to serve as a foundation for developing frugal living behaviors that are more contextual and closely aligned with students’ everyday experiences. Based on this perspective, this study developed a parenting model that integrates the local wisdom values of Lampung, namely Nengah Nyappur and Nemui Nyimah, to strengthen frugal living behavior among students of SMAS YP UNILA Bandar Lampung. The model was developed using a Research and Development approach guided by the ADDIE framework, which includes needs analysis, design, product development, implementation, and evaluation stages. Data were collected through observations, questionnaires, and documentation involving Grade XI students in the 2025/2026 academic year. The quality of the instruments and the developed product was assessed through validity and reliability testing, while the impact of the model’s implementation was analyzed using N-Gain analysis and the Independent Sample t-test. The final product, in the form of a practical parenting guidebook, received a “very feasible” evaluation from material, media, language, and cultural experts. Its implementation also demonstrated a greater improvement in frugal living behavior in the experimental group compared to the control group. These findings indicate that strengthening parenting practices based on Nengah Nyappur and Nemui Nyimah values can foster attitudes of thrift, responsibility, adaptability, and financial management skills, making it a relevant alternative strategy for character education in addressing contemporary adolescent consumer culture. ABSTRAK Fenomena konsumsi berlebihan yang semakin melekat pada kehidupan remaja di era digital menghadirkan tantangan baru bagi pendidikan karakter, terutama dalam membangun kebiasaan mengelola keuangan secara bijaksana. Di tengah kondisi tersebut, nilai-nilai budaya lokal memiliki potensi untuk dijadikan landasan pembentukan perilaku hidup hemat yang lebih kontekstual dan dekat dengan kehidupan peserta didik. Berangkat dari pemikiran tersebut, penelitian ini menghasilkan sebuah model pola asuh yang mengintegrasikan nilai kearifan lokal Lampung, yaitu Nengah Nyappur dan Nemui Nyimah, untuk memperkuat perilaku frugal living siswa SMAS YP UNILA Bandar Lampung. Pengembangan model dilakukan melalui pendekatan Research and Development dengan kerangka ADDIE yang mencakup proses analisis kebutuhan, perancangan, pengembangan produk, implementasi, dan evaluasi. Data diperoleh dari observasi, angket, serta dokumentasi pada siswa kelas XI tahun ajaran 2025/2026. Kualitas instrumen dan produk dianalisis melalui pengujian validitas serta reliabilitas, sedangkan dampak penerapan model dikaji menggunakan analisis N-Gain dan Independent Sample T-Test. Produk akhir berupa buku panduan praktis memperoleh penilaian sangat layak dari ahli materi, media, bahasa, dan budaya. Implementasinya juga menunjukkan peningkatan perilaku frugal living yang lebih baik pada kelas eksperimen dibandingkan kelas kontrol. Temuan ini mengindikasikan bahwa penguatan pola asuh berbasis Nengah Nyappur dan Nemui Nyimah mampu mendorong terbentuknya sikap hemat, tanggung jawab, kemampuan beradaptasi, serta kecakapan mengelola keuangan, sehingga relevan digunakan sebagai alternatif strategi pendidikan karakter dalam menghadapi budaya konsumtif remaja masa kini.